Incidence and Risk Factors of Postoperative Neuropsychiatric Dysfunctions After Deep Brain Stimulation Surgery in Patients with Parkinson's Disease: A Prospective Cohort Study - XIE Sining; JIANG Chenguan; LI Xiangjiahui; HAN Ruquan; YANG Zhou; LI Bingxin; SHI Lin (Xiehe Yixue Zazhi)
ObjectiveTo investigate the incidence of postoperative neuropsychic dysfunction (PND) in Parkinson's disease (PD) patients undergoing deep brain stimulation (DBS) and to analyze its influencing factors.MethodsA prospective study was conducted between January 2020 and December 2022, recruiting PD patients from the Functional Neurosurgery Outpatient Clinic of Beijing Tiantan Hospital, Capital Medical University. All patients were scheduled to undergo bilateral subthalamic nucleus (STN)-DBS surgery. Perioperative clinical data were collected, and PND (outcome measure) within 3 days postoperatively was assessed using the Montreal cognitive assessment (MoCA), mini-mental state examination (MMSE), Hamilton depression and anxiety scales, and 3-minute diagnostic interview for confusion assessment method (3D-CAM). Multivariate Logistic regression was used to analyze the influencing factors of PND.ResultsA total of 216 PD patients were enrolled. Within 3 days after DBS surgery, 77 patients (35.6%) developed PND, including 24 cases (31.2%) of depression or worsening depression, 16 cases (20.8%) of anxiety or worsening anxiety, 13 cases (16.9%) of cognitive decline, and 24 cases (31.2%) of delirium. Univariate analysis revealed that dural opening method, dural opening time, intraoperative improvement rate of the unified Parkinson's disease rating scale -Ⅲ (UPDRS-Ⅲ) score, and postoperative intracranial air volume were significantly different between PND and non-PND patients (all P < 0.05). Multivariate Logistic regression analysis showed that female sex (OR=2.468, 95% CI: 1.077-5.657, P=0.033) and postoperative intracranial air volume (OR=1.217, 95% CI: 1.096-1.351, P < 0.001) were independent risk factors for PND, while a higher intraoperative UPDRS-Ⅲ improvement rate was a protective factor (OR=0.894, 95% CI: 0.863-0.925, P < 0.001).ConclusionsPD patients have a high incidence of PND after DBS surgery. Sex, postoperative intracranial air volume, and the degree of improvement in PD motor symptoms can influence the risk of PND. These findings highlight the importance of individualized management based on sex, improving surgical techniques, and enhancing monitoring of neuropsychiatric status to optimize the efficacy of DBS surgery.